Memahami Pengalaman dan Dampak Psikologis pada Tindak Pidana Kekerasan Seksual bagi Korban dan Pelaku dengan Menggunakan Pendekatan Asosiasi Kata - Pujiarohman, Pujiarohman; Syamsun, Arfi; Harahap, Ida Lestari; Herlina, Lenny; Wahid, Lalu Abdurrachman (Lembaga Yasin AlSys, 2025)
This study aims to analyze the differences in psychological responses between victims and perpetrators of sexual violence using Carl Gustav Jung's analytical psychology theory approach. The research method used is the word association method, this study explores aspects of personality, such as Persona, Shadow, Archetype, and Complex, to identify the psychological dynamics that influence the behavior and perception of these two groups. The results showed that victims tend to display a stable Persona, supported by elements of family and nature archetypes as a mechanism for healing and emotional recovery. Meanwhile, perpetrators show the use of a manipulative Persona to control the surrounding environment and tend to dominate, which is reinforced by the hero and superiority archetypes. The victim's Shadow mostly contains anxiety and fear related to trauma, while the perpetrator's Shadow is more filled with aggressive traits and lack of empathy. The complexes that appear in victims are related to inferiority and social support, while perpetrators show a superiority complex that emphasizes dominance and manipulation. These fundamental differences provide insight into how victims and perpetrators respond to their life experiences and how psychotherapy approaches can be tailored based on their respective needs. This study offers a new perspective in understanding the psychological dynamics of victims and perpetrators of sexual violence and has the potential to contribute to more effective therapeutic interventions.